A silicon-carbon / MXene / rGO composite negative electrode material with a three-dimensional porous structure

CN123017910APending Publication Date: 2026-10-30BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610658148.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,硅负极在充放电过程中伴随高达>300%的体积膨胀,导致以下致命缺陷:不稳定的固体电解质界面(SEI)层;活性颗粒粉化、破裂,失去电接触;导电网络崩塌,极化增大,容量快速衰减;固有的低电导率(10-5~ 10-3S cm-1)和低锂离子扩散系数(10-14~ 10-13cm s-1)导致其倍率性能差

Benefits of technology

[0015]本发明采用原位聚合法与化学还原法相结合的创新工艺,实现了对硅纳米颗粒的多尺度精准包覆。其中,首先在氨基化硅颗粒表面上原位聚合酚醛树脂后碳化,再与二维材料MXene/rGO组装成三维多孔网络,形成内部碳层机械缓冲与外部三维导电骨架应力分散的双重保护结构。该结构不仅通过碳层有效缓解硅的体积膨胀,更借助MXene/rGO的三维连续导电通路和强韧多孔骨架及促进了界面电子转移,显著提高了电极结构稳定性与离子/电子传输效率,协同增强了电极的力学稳定性和电荷传输动力学。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017910A_ABST
    Figure CN123017910A_ABST
Patent Text Reader

Abstract

The present disclosure belongs to the field of electrochemistry and new energy technology, and particularly relates to a preparation of a three-dimensional porous structure silicon-carbon / MXene / rGO composite negative electrode material and its application in lithium ion batteries. The method is to assemble a three-dimensional porous network by carbonizing the in-situ polymerization of amino-silicon particles with phenolic resin, and then assembling with two-dimensional material MXene / rGO, to form a double protection structure of internal carbon layer mechanical buffer and external three-dimensional conductive skeleton stress dispersion. The structure not only effectively relieves the volume expansion of silicon through the carbon layer, but also inhibits the structural pulverization and conductive network degradation of the electrode in long cycle by means of the three-dimensional continuous conductive path and strong and tough porous skeleton of MXene / rGO, significantly improving the charge transport kinetics of the electrode. The obtained material has a capacity of 1016 mAh g at a current density of 2 A g ‑1 The capacity is 447 mAh g after 200 cycles ‑1 , 2 A g 1 The capacity is 1016 mAh g at a current density of 2 A g 1 , showing excellent cycle stability and rate performance. The process conditions are mild, and the raw materials are easy to obtain, providing an effective strategy for constructing high-stability silicon-based negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemistry and new energy technology, specifically relating to the preparation of a three-dimensional porous silicon-carbon / MXene / rGO composite anode material and its application in lithium-ion batteries. Background Technology

[0002] Lithium-ion batteries, as the most competitive electrochemical energy storage devices currently available, have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage. With the market's continued increase in demand for energy density, the development of high-specific-capacity anode materials to overcome the bottlenecks of existing systems has become particularly urgent.

[0003] Silicon anodes are known for their extremely high theoretical specific capacity (4200 mAh g). -1 Lower lithium intercalation potential (~0.4 V vs. Li / Li) + Silicon anodes, with their abundant crustal reserves, are considered ideal candidate materials. However, silicon anodes experience volume expansion of up to >300% during charge and discharge, leading to the following fatal defects: an unstable solid electrolyte interphase (SEI) layer; pulverization and breakage of active particles, resulting in loss of electrical contact; collapse of the conductive network, increased polarization, and rapid capacity decay; and inherently low conductivity (10⁻⁶ ppm). -5 ~ 10 -3 S cm -1 ) and low lithium-ion diffusion coefficient (10 -14 ~ 10 -13 cm s -1 This results in poor rate performance.

[0004] MXene (chemical formula M) n+1 X n T x Where M is a transition metal such as Ti, V, or Mo, X is C or N, and T is T. x (Representing surface functional groups such as -OH, -F, and -O) possessing metallic-grade electrical conductivity (≈10). 5 S cm -1High Young's modulus (≈330 GPa), abundant surface functional groups, and good hydrophilicity. Reduced graphene oxide (rGO) sheets possess a large specific surface area and high flexibility, enabling them to synergistically construct a continuous, flexible, and conductive integrated three-dimensional framework with MXene. This framework not only provides ample space for loading active materials, but its interconnected porous structure also facilitates rapid electrolyte penetration and ion transport. Simultaneously, this work utilizes in-situ phenolic resin polymerization and carbonization processes to construct a uniform amorphous carbon shell on the surface of silicon particles. This carbon layer serves as an internal buffer layer, effectively constraining the drastic volume deformation of silicon during lithium insertion / extraction; its excellent conductivity improves conductivity and rate performance; and the carbon layer also significantly reduces direct contact between silicon and the electrolyte, minimizing side reactions and enhancing interfacial stability.

[0005] Therefore, multi-scale, strong interfacial coupling of high-capacity silicon-carbon particles, highly conductive MXene, and structurally supporting rGO to achieve adaptive adjustment of volumetric stress and persistent maintenance of the conductive network during long-cycle cycling remains a cutting-edge research direction in the design of high-energy-density lithium-ion battery anode materials. Summary of the Invention

[0006] The purpose of this invention is to provide a three-dimensional porous silicon-carbon / MXene / rGO composite anode material. By assembling silicon-carbon particles with two-dimensional MXene / rGO materials into a three-dimensional porous network, a dual protective structure is formed, consisting of an internal carbon layer for mechanical buffering and an external three-dimensional conductive framework for stress dispersion. This solves the problems of conductive network breakage, interface peeling, and capacity decay caused by silicon volume expansion, thereby improving the cycle stability and kinetic performance of the anode.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The preparation of a three-dimensional porous silicon-carbon / MXene / rGO composite anode material and its application in lithium-ion batteries includes the following steps: (1) Preparation of MXene dispersion: Ti3AlC2MAX phase was etched in situ using a LiF / HCl mixed solution, and then a single-layer or few-layer Ti3AlC2MXene aqueous dispersion was obtained after water washing, ultrasonic exfoliation and centrifugation; (2) Pretreatment of silicon-based materials: Silicon nanoparticles and silane coupling agents are surface modified in deionized water to obtain positively charged aminated silicon particles. (3) In-situ polymerization coating and carbonization: Phenolic resin precursor is added to the aminated silicon particle dispersion system for in-situ polymerization reaction, and carbonization is carried out under an inert atmosphere to obtain silicon-carbon composite material. (4) Assembly of three-dimensional porous structure: The silicon-carbon composite material obtained in step (3), the MXene dispersion obtained in step (1) and the GO dispersion are stirred and dispersed under inert gas protection in proportion, chemically reduced with oxalic acid, and three-dimensional porous structure material is obtained by low temperature hydrothermal and freeze drying methods.

[0008] Preferably, the MXene in step (1) is selected from Ti3C2T. x The temperature is 30-40 ℃ and the time is 20-30 h.

[0009] Preferably, the silane coupling agent in step (2) is APTES; the temperature is room temperature and the time is 12-36 h.

[0010] Preferably, the phenolic resin precursor in step (3) comprises resorcinol and formaldehyde in a molar ratio of 1:1.5. 3.0; and add ammonia to adjust the pH value; the temperature is 40-60 ℃, and the time is 20-30 h.

[0011] Preferably, the carbonization process is carried out in an argon atmosphere at a temperature of 650-850 °C for 2-5 h.

[0012] Preferably, in step (4), the mass ratio of silicon carbide particles, MXene solid to GO solid is (6). 10):(0.5 2):(1 4); The amount of oxalic acid added is 10% of the mass of the silicon carbide particles. 30%.

[0013] The present invention also provides the application of the three-dimensional porous silicon-carbon / MXene / rGO composite anode material described in the above technical solution in lithium-ion batteries.

[0014] The purpose of this invention is to provide a three-dimensional porous silicon-carbon / MXene / rGO composite anode material. By assembling silicon-carbon particles with two-dimensional MXene / rGO materials into a three-dimensional porous network, a dual protective structure is formed, consisting of an internal carbon layer for mechanical buffering and an external three-dimensional conductive framework for stress dispersion. This solves the problems of conductive network breakage, interface peeling, and capacity decay caused by silicon volume expansion, thereby improving the cycle stability and kinetic performance of the anode.

[0015] This invention employs an innovative process combining in-situ polymerization and chemical reduction to achieve precise multi-scale coating of silicon nanoparticles. First, phenolic resin is in-situ polymerized on the surface of aminated silicon particles and then carbonized. This resin is then assembled with the two-dimensional material MXene / rGO to form a three-dimensional porous network, creating a dual protective structure with an internal carbon layer providing mechanical buffering and an external three-dimensional conductive framework for stress dispersion. This structure not only effectively alleviates the volume expansion of silicon through the carbon layer but also, with the help of the three-dimensional continuous conductive pathways and robust porous framework of MXene / rGO, promotes interfacial electron transfer, significantly improving the electrode structural stability and ion / electron transport efficiency, and synergistically enhancing the electrode's mechanical stability and charge transport kinetics. Attached Figure Description

[0016] Figure 1 The images show (a) a scanning electron microscope (SEM) image of the cross-section of a monolayer MXene film and (b) a scanning electron microscope (SEM) image of aminated silicon nanoparticles prepared in Example 1 of this invention. from Figure 1 As can be seen, the monolayer MXene film exhibits a clear layered stacking structure with uniform interlayer spacing, confirming the successful exfoliation of the Al atomic layer and the monolayer characteristics. Its abundant interlayer voids can provide a fast channel for ion transport. from Figure 1 As can be seen from b, the aminated silicon particles are well dispersed, with a uniform particle size distribution and no obvious agglomeration on the surface, providing active sites for subsequent binding with carbon precursors.

[0017] Figure 2 The images shown are (a) scanning electron microscope (SEM) images and (be) corresponding elemental distribution diagrams of Si, C, O, and N for the silicon-carbon composite material prepared in Example 1 of this invention. from Figure 2 As can be seen, the silicon-carbon composite particles have a regular morphology and a relatively uniform particle size distribution. from Figure 2 As can be seen from the results, the signal distributions of Si, C, and O elements are highly overlapping and uniform, confirming that the silicon particles were successfully and uniformly coated by the phenolic resin-derived carbon layer; the uniform distribution of N elements confirms the successful grafting of the silane coupling agent.

[0018] Figure 3 The images shown are (a) X-ray diffraction (XRD) pattern and (b) Raman pattern of the silicon-carbon composite material prepared in Example 1 of this invention. from Figure 3 As can be seen from the absence of obvious carbon (002) crystal plane characteristic peaks, it indicates that the coated carbon is mainly amorphous carbon; the absence of SiC or SiO2 impurity peaks indicates that the surface carbon layer has not undergone excessive carbonization reaction. from Figure 3b shows that a higher I D / I G The strength ratio confirms that the coated carbon layer has a highly disordered graphitic microcrystalline structure with abundant defects, which can provide additional lithium storage sites.

[0019] Figure 4 The images shown are (a) scanning electron microscope (SEM) images and (be) corresponding elemental distribution diagrams of Si, C, O, and Ti for the silicon-carbon / MXene / rGO composite anode material prepared in Example 1 of this invention. from Figure 4 As can be seen, the silicon-carbon / MXene / rGO composite material exhibits an irregular composite morphology of flakes and particles after grinding, retaining the skeletal features of the three-dimensional network. from Figure 4 As can be seen, the signal distributions of Si, C, and Ti elements are highly overlapping and uniform, confirming that the silicon particles have been successfully embedded in the three-dimensional continuous conductive network jointly constructed by MXene and rGO.

[0020] Figure 5 The charge-discharge curves are for the half-cell of the silicon-carbon / MXene / rGO composite anode material prepared in Example 1 of this invention. Detailed Implementation

[0021] The purpose of this invention is to provide a three-dimensional porous silicon-carbon / MXene / rGO composite anode material. By assembling silicon-carbon particles with two-dimensional MXene / GO materials into a three-dimensional porous network, a dual protective structure is formed, consisting of an internal carbon layer for mechanical buffering and an external three-dimensional conductive framework for stress dispersion. This solves the problems of conductive network breakage, interface peeling, and capacity decay caused by silicon volume expansion, thereby improving the cycle stability and kinetic performance of the anode.

[0022] Unless otherwise specified, the present invention does not have special requirements for the source of raw materials used. Silicon nanoparticles, MXene dispersion (prepared by MAX phase etching), GO dispersion (prepared using a modified Hummer's method), resorcinol, formaldehyde, etc. are all prepared using commercially available products or conventional methods well known to those skilled in the art.

[0023] In this invention, the etching temperature of the MAX phase is 30-40 °C, and the time is 20-30 h, to ensure complete removal of the Al layer and obtain a monolayer Ti3C2T. xThe silicon-carbon composite particles are a composite of nano-silicon particles and a porous carbon framework, prepared by in-situ carbonization of nano-silicon modified with phenolic resin using a silane coupling agent. Calcination temperature and time: The silicon-carbon particles are calcined at 600-800 ℃ for 2-4 h. If the temperature is too low (<600 ℃), the phenolic resin carbonization is incomplete, resulting in a loose porous carbon framework structure that cannot effectively buffer the volume expansion of silicon. If the temperature is too high (>800 ℃), the carbon framework becomes excessively graphitized, reducing porosity and hindering lithium-ion diffusion.

[0024] In this invention, the material ratio is a key parameter: when the proportion of silicon-carbon composite particles is too low (mass ratio < 6), the strong van der Waals forces between rGO and MXene nanosheets will cause the nanosheets to self-stack, resulting in a reduction in specific surface area and reactive sites, and restricted ion diffusion; when the proportion is too high (mass ratio > 10), the loading of silicon-carbon particles is too large, and some particles cannot be fully encapsulated and connected by the two-dimensional material network, which easily leads to direct aggregation and rapid capacity decay during cycling.

[0025] As one embodiment, the tap density of the silicon-carbon / MXene / rGO composite anode material is ≥0.2 g cm⁻¹. -3 Electrode conductivity ≥100 S cm -1 .

[0026] This invention utilizes an innovative process combining in-situ polymerization and chemical reduction to achieve precise multi-scale coating of silicon nanoparticles, forming a dual protective structure with an internal carbon layer providing mechanical buffering and an external three-dimensional conductive framework for stress dispersion. This structure not only effectively mitigates silicon volume expansion through the carbon layer but also leverages the three-dimensional continuous conductive pathways and robust porous framework of MXene / rGO to promote interfacial electron transfer, significantly improving electrode structural stability and ion / electron transport efficiency, and synergistically enhancing the electrode's mechanical stability and charge transport kinetics.

[0027] As one embodiment, the method for preparing the electrode includes the following steps: The active material, conductive agent, binder and water are mixed, and the resulting slurry is coated on the current collector. After drying, it is cut to obtain the electrode sheet.

[0028] To achieve the above-mentioned objectives, the present invention provides the following technical solution: a three-dimensional porous silicon-carbon / MXene / rGO composite anode material, comprising a silicon-carbon / MXene / rGO composite material, a Super P conductive agent, and a CMC binder, wherein the parameters and proportions of each component are optimized as follows: In one embodiment, the active material is a silicon-carbon / MXene / rGO composite material, and the mass ratio of the active material, Super P conductive agent, and CMC binder is 6~9:3~1:3~1, specifically 8:1:1. The present invention does not have a specific limitation on the amount of water used, as long as a uniform slurry is obtained. The mixing involves stirring and homogenizing. The present invention does not have a specific limitation on the stirring rate and time, or the homogenizing process, as long as the materials are mixed to form a uniform slurry. The coating is done by scraping. The current collector is copper foil. The drying is vacuum drying. The drying temperature is 50~70 ℃, specifically 60 ℃, and the drying time is 10~14 h, specifically 12 h.

[0029] This invention also provides a lithium-ion battery, comprising a negative electrode, an electrode sheet, an electrolyte, and a separator; the active material used in the electrode sheet is the silicon-carbon / MXene / rGO composite material described in the above-mentioned technical solution; the electrolyte comprises a lithium salt, a solvent, and additives; the lithium salt is lithium hexafluorophosphate (LiPF6); the solvent comprises ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC); the volume ratio of ethylene carbonate, diethyl carbonate, and dimethyl carbonate is 1:1:1; the additives are fluoroethylene carbonate (FEC) and vinylene carbonate (VC), and their addition amounts are 5% and 1% of the total mass of the electrolyte, respectively; the concentration of lithium salt in the electrolyte is 1 mol / L. -1 The diaphragm is Celgard 2500.

[0030] As one embodiment, the lithium-ion battery is prepared by encapsulating the electrode, lithium sheet, separator and electrolyte into a lithium-ion battery in a glove box filled with Ar gas; the lithium-ion battery is a CR2025 type lithium-ion battery.

[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention, but they should not be construed as limiting the scope of protection of the present invention.

[0032] Example 1 The silicon-carbon / MXene / rGO composite anode material based on a three-dimensional porous structure in this embodiment is prepared by the following steps: 0.99 g of LiF is weighed and placed in 10 mL of HCl (12 mol L). -1 In a solution containing 1 g of Ti3AlC2MAX phase precursor powder, stir for 30 min until LiF is completely dissolved. Then, add 1 g of Ti3AlC2MAX phase precursor powder to the above mixed solution in small amounts several times, and etch in a water bath for 24 h at an etching temperature of 35 °C. After cooling to room temperature, centrifuge and wash until neutral, and obtain monolayer or few-layer MXene dispersions by multiple ultrasonic exfoliations (power 300 W, time 1 h).

[0033] 500 mg of commercial silicon nanoparticles (approximately 30 nm in diameter) were dispersed in 100 mL of deionized water. 1 mL of ATPES was added, and the mixture was magnetically stirred at room temperature for 24 h. After the reaction, the mixture was filtered, thoroughly washed with deionized water, and then vacuum-dried at 60 °C for 12 h to obtain aminated silicon particles. 200 mg of the aminated silicon particles were dispersed in 30 mL of deionized water and sonicated for 1 h. 0.1 mL of ammonia (28 wt%), 560 mg of resorcinol, and 760 μL of formaldehyde (37 wt%) were added sequentially to the above dispersion system, and the mixture was stirred at 50 °C for 24 h to achieve uniform polymerization and coating of phenolic resin on the surface of the aminated silicon particles. The product was then subjected to argon atmosphere at 5 °C for 1 min. -1 The temperature was increased to 750 °C at a certain rate, carbonized for 3 h, and then naturally cooled to obtain a silicon-carbon composite material.

[0034] Weigh 48 mg of silicon-carbon composite material and 1 mL of MXene dispersion (6 mg / mL). -1 ) and 1.6 mL GO dispersion (7.5 mg / mL) -1 The mixture was dispersed in 20 mL of deionized water, and stirred at room temperature for 4 h after purging with argon gas. 100 mg of oxalic acid was added, and the mixture was reacted in a water bath at 70 ℃ for 12 h. The mixture was washed three times with deionized water, then freeze-dried and vacuum-dried at -80 ℃ for 48 h to obtain a three-dimensional porous material.

[0035] Application Example 1 The silicon-carbon / MXene / rGO composite anode material prepared in Example 1 was used as the active material. It was mixed with Super P and CMC at a mass ratio of 8:1:1. Water was added, and the mixture was stirred and homogenized to form a uniform slurry. The slurry was then uniformly coated onto a copper current collector foil and dried in a vacuum oven at 60 °C for 12 h. Finally, it was cut into electrode sheets with a diameter of 8 mm. Celgard 2500 with a diameter of 16 mm was used as the separator. A mixed solution of 1 M LiPF6 dissolved in EC:DMC:EMC (volume ratio 1:1:1) with the addition of 5% FEC and 1% VC was used as the electrolyte. The mixture was then encapsulated in an argon-filled glove box to form a CR 2025 type lithium-ion battery.

[0036] Test Example 1 The battery assembled for use case 1 was subjected to charge / discharge performance testing under the following conditions: constant current charge / discharge mode; current density of 0.1 A g. -1 Voltage window 0.01-2.0 V (vs. Li + / Li). The battery assembled in Application Example 1 was in 0.1 A g.-1 The first three charge-discharge curves at current density. (Example) Figure 4 As shown, the first-cycle discharge / charge specific capacity is 2276 mAh g. -1 and 1697 mAh g -1 The initial coulombic efficiency was 74.5%. The capacity decay slowed down significantly and the voltage plateau stability was enhanced in the second and third charge-discharge curves, indicating that the three-dimensional porous structure constructed by the internal carbon coating layer and the external MXene / rGO three-dimensional conductive network rapidly formed a stable interface in the initial cycle, effectively suppressing the continuous side reactions between silicon particles and electrolyte and improving the reversibility of electrochemical reaction.

[0037] Test Example 2 Cycle performance testing was performed on the batteries assembled for use case 1, such as... Figure 5 As shown, the battery assembled in Application Example 1 maintained a specific capacity of 447 mAh g⁻¹ after 200 cycles at a current density of 0.5 A g⁻¹, demonstrating excellent capacity retention and structural stability. Figure 4 (b) It can be seen that the battery assembled in Application Example 1 exhibits good rate performance. The specific capacities at 0.1 A g⁻¹, 0.3 A g⁻¹, 0.5 A g⁻¹, 0.8 A g⁻¹, 1 A g⁻¹, 2 A g⁻¹ and 0.1 A g⁻¹ are 2083 mAh g⁻¹, 1778.3 mAh g⁻¹, 1588.7 mAh g⁻¹, 1416.8 mAh g⁻¹, 1299.1 mAh g⁻¹, 1016.4 mAh g⁻¹ and 1511.3 mAh g⁻¹, respectively. The material can still provide a high reversible specific capacity of 1016.4 mAh g⁻¹ at a high current of up to 2 A g⁻¹. When the current density is restored to 0.1 A g⁻¹, the specific capacity quickly recovers to about 1511.3 mAh g⁻¹, which fully demonstrates the high efficiency of the internally constructed efficient electron / ion dual continuous transport channel and the fast reaction kinetics.

[0038] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon / MXene / rGO composite anode material based on a three-dimensional porous structure, characterized in that, Includes the following steps: (1) Preparation of MXene dispersion: Ti3AlC2 MAX phase was etched in situ using a LiF / HCl mixed solution, and then a single-layer or few-layer Ti3AlC2 MXene aqueous dispersion was obtained after water washing, ultrasonic exfoliation and centrifugation; (2) Pretreatment of silicon-based materials: Silicon nanoparticles and silane coupling agents are surface modified in deionized water to obtain positively charged aminated silicon particles. (3) In-situ polymerization coating and carbonization: Phenolic resin precursor is added to the aminated silicon particle dispersion system for in-situ polymerization reaction, and carbonization is carried out under an inert atmosphere to obtain silicon-carbon composite material. (4) Assembly of three-dimensional porous structure: The silicon-carbon composite particles obtained in step (3), the MXene dispersion obtained in step (1) and the GO dispersion are stirred thoroughly under inert gas protection in proportion, chemically reduced with oxalic acid, and three-dimensional porous structure material is obtained by low temperature hydrothermal and freeze drying methods.

2. The method according to claim 1, characterized in that... The MXene mentioned in step (1) is a two-dimensional transition metal carbide selected from Ti3C2T x The sheet thickness is 0.5-1.5 nm, the lateral dimension is 0.5-5 μm, and the conductivity is 10. 4 -10 5 S cm -1 .

3. The preparation method according to claim 1, characterized in that... The silane coupling agent in step (2) is APTES; the temperature is room temperature and the time is 12-36 h.

4. The preparation method according to claim 1, characterized in that... In step (3), the molar ratio of resorcinol to formaldehyde is 1:(1.8-2.5); the temperature is 48-55 ℃ and the time is 22-26 h.

5. The preparation method according to claim 1, characterized in that... In step (4), the mass ratio of silicon-carbon composite particles, MXene solid, and GO solid is (7.5-8.5):(0.8-1.2):(1.5-2.5); the mass of oxalic acid is 18%-25% of the mass of silicon-carbon composite particles.

6. The silicon-carbon composite anode material according to claim 1, characterized in that... The carbonization is carried out in an argon atmosphere at a temperature of 650-850 °C for 2-5 h.

7. The preparation method according to claim 1, characterized in that... In step (4), the reaction temperature after adding oxalic acid is 65-75 ℃ and the reaction time is 10-15 h.

8. An application of lithium-ion batteries, characterized in that, The silicon-carbon / MXene / rGO composite anode material as described in claim 1 is applied to lithium-ion battery anode materials.